Functional MRI for Acute Covert Consciousness: Emerging Data and Implementation Case Series - Boerwinkle, Varina L.; Gillette, Kirsten; Rubinos, Clio A.; Broman-Fulks, Jordan; Aseem, Fazila; DeHoff, Grace K.; Arhin, Martin; Cediel, Emilio; Strohm, Tamara (Seminars in Neurology, 2023)
Although research studies have begun to demonstrate relationships between disorders of consciousness and brain network biomarkers, there are limited data on the practical aspects of obtaining such network biomarkers to potentially guide care. As the state of knowledge continues to evolve, guidelines from professional societies such as the American and European Academies of Neurology and many experts have advocated that the risk–benefit ratio for the assessment of network biomarkers has begun to favor their application toward potentially detecting covert consciousness. Given the lack of detailed operationalization guidance and the context of the ethical implications, herein we offer a roadmap based on local institutional experience with the implementation of functional MRI in the neonatal, pediatric, and adult intensive care units of our local government-supported health system. We provide a case-based demonstrative approach intended to review the current literature and to assist with the initiation of such services at other facilities.
Keywords: functional connectivity; coma; prognosis; resting-state fMRI; acute brain injury; disorders of consciousness